Art meets science and spirituality in a changing economy - Wijers, Louvrien; Harris, Maxine; Rochlin, Sheldon (Amstersdam Asset Foundation, 1992)
Drawn from the Conference in Amsterdam in September 1990. Among the topics discussed are creativity, coherance, wholeness and the implicate order. includes interviews with Robert Rauschenberg at his Studio in Florida whre he is seen creating a new work of art and exhibit, Smith David Bohm explaining his theory od the "implicate order" and with Dalai Lama speaking on the nature od mind and on his personal feelings as leader of the Tibetans in exile.
VHS
Editor, Morgan Harris, Sheldon Rochlin
Keywords: Perception -- Congresses; Conciousness; Culture; Creativity ability; Creation (Literary, artistic, etc.)